Skill in a Globalized World: Migrant Workers in the Gold Jewelry‐Making Industry in Kerala, India. Issue 3 (September 2014) - Maruthur, Sumeetha Mokkil
<x xml:space="preserve">Abstract</x> The article analyzes the labor process in the gold jewelry‐making industry in Kerala, the southern state of India, particularly focusing on a single dimension "skill." Informal manufacturing has emerged as a substantial income and employment‐generating activity in the post‐liberalization (1990s) period in the country. This was accompanied by the accentuating internal migration throughout India aided by strong social networks and commissioned agents. The gold jewelry making in Kerala like in other parts of India was organized in caste lines up to the 1960s, dominated by the Viswakarma caste. Work was carried out in response to local orders by a single craftsman, assisted by an apprentice. The burgeoning market economy and the enforcement of deregulation had profound effects on the production relations, hierarchy, and organization in the industry. The deregulation of the gold industry ushered in different kind of workers into the industry. The core of the article is an examination of the variety of skill requirements in the industry and the position and place of workers—local workers, women workers, and migrants in the industry.